Effects of reduction of adenosine deaminase activity in the serum of dogs naturally infected by Ehrlichia canis and Hepatozoon canis - Bottari N.B. (2015)
© 2015, Springer-Verlag London.Ehrlichia canis and Hepatozoon canis have been reported infecting a variety of Carnivora species worldwide, including domestic dogs and wild canids. Since both diseases can follow their course while the infected animals remain asymptomatic, assessments of different parameters that may help toward reaching a more accurate diagnosis are welcome. In this regard, the aim of the present study was to assess the activity of adenosine deaminase (ADA) in serum from naturally infected dogs. Forty-nine samples from dogs were used in our study: 15 positive for E. canis (8 asymptomatic and 7 symptomatic animals); 8 positive for H. canis; 14 with mixed infection; and 12 uninfected (used with control). Our results showed that the ADA activity was lower (P < 0.001) in serum from dogs with both infections singly and with mixed infection, in comparison with the uninfected animals (P < 0.001). The symptomatic dogs for E. canis had lower ADA activity when compared with asymptomatic dogs by H. canis (P < 0.01). Therefore, ADA activity reduces in positive dogs for E. canis and H. canis, which can be related to an inflammatory response against infection.